Biology Reference
In-Depth Information
For our main problem of CpG identification, the probability P
(
x
)
of a DNA
sequence of nucleotides x
x l is not of much interest by itself but we will
need it to compute the posterior probabilities P
=
x 1 x 2 ···
l ,
that symbol x t in the observed sequence was emitted from state k , which can then be
used for decoding.
Since
t
=
k
|
x
),
k
Q
,
t
=
1
,
2
,...,
P
(
x
t =
k
)
P
t =
k
|
x
) =
,
(9.3)
P
(
x
)
we need a recursive algorithm for computing P
(
x
t =
k
)
. The Markov property of
the hidden process makes this possible:
P
(
x
t =
k
) =
P
(
x 1 x 2 ···
x t t =
k
)
P
(
x t + 1 x t + 2 ···
x l |
x 1 x 2 ···
x t t =
k
)
=
P
(
x 1 x 2 ···
x t t =
k
)
P
(
x t + 1 x t + 2 ···
x l | π t =
k
).
(9.4)
The first line is a direct application of the conditional probability formula where the
probability that x is generated with
k at time t is given as the product of the
probabilities of the following events: (1) symbols x 1 x 2 ···
π t
=
x t are emitted up to time t
and the process is in state k at time t , and (2) conditioned upon the event (1), the rest
of the emitted sequence is x t + 1 x t + 2 ···
x l . The second line follows from the Markov
property of the hidden process and restates that the probability to emit the sequence
x t + 1 x t + 2 ···
x l depends only on the state of the process at time t .
Notice that the P
(
x 1 x 2 ···
x t t =
k
)
are exactly the probabilities f k (
t
)
, which are
computed from the forward algorithm. Denote b k (
t
) =
P
(
x t + 1 x t + 2 ···
x l | π t
=
k
)
.
Equation ( 9.4 ) can now be re-written as
P
(
x
t =
k
) =
f k (
t
)
b k (
t
).
(9.5)
are computed by the backward algorithm .Webeginby
initializing the algorithm for t
The probabilities b k (
t
)
=
l where, since x l is the last observed symbol,
π l + 1
=
E is the end state (that does not emit a symbol). Thus b k (
) =
l + 1
=
l
P
| π l =
) =
,
E
Q , since the sequence goes to the end state E with probability 1.
Once we know b k (
k
1
k
l
)
for all k
Q , for any of the values t
=
l
1
,
l
2
,...,
1
we can compute
b j (
t
) =
P
(
x t + 1 x t + 2 ···
x l | π t =
j
)
=
t + 1 =
| π t =
)
e k (
x t + 1 )
(
x t + 2 ···
x l | π t + 1 =
)
P
k
j
P
k
k
Q
=
a jk e k (
x t + 1 )
b k (
t
+
1
).
k
Q
The justification is as follows: At time t
+
1 the process can transition from j to any
other state k
Q (this happens with probability a jk )
,emit x t + 1 (this happens with
probability e k (
x t + 1 ))
, and, being in state k at time t
+
1, emit the rest of the sequence
x t + 2 ···
x l (which happens with probability b k (
t
+
1
))
.
 
Search WWH ::




Custom Search